2003
DOI: 10.1046/j.1365-4362.2003.01756_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline‐induced cutaneous pigmentation

Abstract: A 76‐year‐old man receiving long‐term prednisone therapy for rheumatoid arthritis had a four‐part intertrochanteric fracture after a fall. The patient underwent an open reduction with internal fixation and dynamic hip screw placement. Two months later, when the patient presented with significant pain and difficulty ambulating, radiographs revealed dissociation of the compression screw from the femoral head. At the time of removal of failed hardware, a total hip replacement procedure was aborted when intraopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…We propose that minocycline has no direct effects on melanin synthesis or tyrosinase activity (data not shown), and the up-regulated melanin synthesis by minocycline is most likely a consequence of an increase of melanocyte viability. Collective data from clinical application have revealed that skin pigmentation occurs in some rheumatoid patients with chronic minocycline administration (36,37). Although the underlying mechanism has not yet been elucidated, it has been observed that minocyclineinduced pigment deposit in papillary dermis but not in epidermis has been observed (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that minocycline has no direct effects on melanin synthesis or tyrosinase activity (data not shown), and the up-regulated melanin synthesis by minocycline is most likely a consequence of an increase of melanocyte viability. Collective data from clinical application have revealed that skin pigmentation occurs in some rheumatoid patients with chronic minocycline administration (36,37). Although the underlying mechanism has not yet been elucidated, it has been observed that minocyclineinduced pigment deposit in papillary dermis but not in epidermis has been observed (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Type III pigmentation presents with diffuse muddy-brown discoloration on photo-exposed skin [23]. In types II and III pigmentation, there is an association between the duration of minocycline intake and the duration of pigmentation reported, with the median duration lasting more than 9 months with cumulative doses [10,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Type III appears muddy‐brown, developing in a generalized, symmetric pattern and accentuated in areas of sun exposure (6). In both alkaptonuria and minocycline‐induced hyperpigmentation, the pigment deposited is believed to resemble melanin (4, 9). If a patient is found to have hyperpigmentation secondary to minocycline, the medication should be stopped to prevent further pigment accumulation.…”
Section: Discussionmentioning
confidence: 99%